A new biomarker in alcohol use disorders: carbohydrate deficient transferrin (cdt) - Ceyhan; Şengül, Cem; Dilbaz, Nesrin; Okay, Tuncer (Journal of Dependence, 2004)
Alcoholism is a serious disorder, which has a prevalence of %13.53 for men, %2.82 for women and %7.9 overall, was characterized by inability to resist desire for alcohol, excessive and frequent alcohol intake, which can disrupt individual’s physical and mental health and also family, work and social adaptation. Objective, sensitive, specific, reliable, economic, easily applicable biological markers are needed for diagnosis, treatment planning and prevention of relapse in alcoholism which can cause many alcohol related physical and mental disorders. Because of this, researchers are going on working for new biomarkers. Carbohydrate Deficient Transferrin (CDT) is new biomarker which is more specific and sensitive than traditional markers and approved by Food and Drug Administration (FDA). It was first reported by Stibler and Kjellin in 1976. Since than many researches were made on CDT and many articles were published on its usage in alcoholism. We investigated Pubmed data base by using key words alcohol, CDT, biomarker and transferrin in the literature published since 1976. And than we used the full text articles we managed to obtain to review literature on Carbohydrate Deficient Transferrin.